Short and long term chorion villi culture discordance. Presentation of a case and theme review - Quiroga de Michelena, María (2008)
We present a prenatal diagnosis case with false negative result in long term villi culture discordant with short term villi culture showing trisomy 21. We discuss possible causes of discordance in this and similar cases and the best way to proceed to ensure correct diagnosis.